ANTIBACTERIAL ACTIVITY OF TARO LEAVES EXTRACTCOMBINED WITH ZnO AND ORGANO-ZnO AGAINST Staphylococcus aureus - Ahmad Hafizullah Ritonga; Imel Santika; Hasni Yaturramadhan Harahap; Barita Aritonang (Universitas Haji Sumatera Utara, 2025)
Staphylococcus aureus is a pathogenic bacterium commonly associated with serious human infections, leading to various health complications. Zinc oxide (ZnO) is well known for its antibacterial properties, while Organo-ZnO, a modified form of ZnO incorporating organic compounds, exhibits even stronger antibacterial potential. Due to their therapeutic properties, Taro leaves (Colocasia esculenta L.) have a long history of traditional use for treating various ailments, including burns and boils. This study aims to identify the active compounds in taro leaves that function as antibacterial agents and to evaluate the combined antibacterial activity of taro leaf extract with ZnO and Organo-ZnO against Staphylococcus aureus. The research was conducted as a laboratory experiment. Phytochemical screening revealed that the taro leaf extract contains alkaloids, flavonoids, tannins, and saponins, which may contribute to its antibacterial effects. Antibacterial activity tests against Staphylococcus aureus showed inhibition zones of 8.5 mm for taro leaf extract, 8.8 mm for 5% ZnO, and 10 mm for 5% Organo-ZnO. The combination of taro leaf extract with 5% ZnO resulted in an inhibition zone of 9.1 mm, while the combination with 5% Organo-ZnO exhibited the highest inhibition zone of 10.7 mm. These results suggest that the ethanol extract of taro leaves possesses significant antibacterial activity against Staphylococcus aureus, and its effectiveness is further enhanced when combined with ZnO and Organo-ZnO. The combination with Organo-ZnO demonstrates the greatest antibacterial potential, indicating its promise for further development in antibacterial applications.